An environmental, social, and governance (ESG) model for multiple criteria analysis of investments - Lombardi Netto, Antonio [UNESP]; Salomon, Valerio A. P. [UNESP]; Ortiz-Barrios, Miguel A. (Wiley, 2025)
The selection of investment alternatives is a decision problem mostly solved by considering three criteria: liquidity, return, and risk. This article proposes a wider investment analysis, considering environmental and social criteria. Therefore, environmental, social, and governance (ESG) principles are considered in investments' multiple criteria decision analysis (MCDA). There are several MCDA methods, so choosing a method is a prior problem in decision-making. In this article, the problem of selecting investment alternatives is divided into sorting and ranking alternatives. The Multi-Attribute Utility Theory (MAUT) was applied for sorting, and the Analytic Hierarchy Process (AHP) was applied for ranking. Identifying these two methods as effective for the problem in question is an initial contribution of this work. The article also presents an ESG multicriteria hierarchical model for analyzing investment alternatives. Finally, the model is tested by analyzing five cooperative companies producing walnuts in the Brazilian Amazon. With the MAUT application, three companies were considered attractive for investment, while the other two were considered unattractive. With the AHP, the three attractive alternatives were ranked from best to worst for investment. Although ESG and MCDA are two fertile research fields, no document was found in the literature review combining ESG and MCDA in investment analysis. This literature gap raises a practical question: When something has not been applied, how can it be applied first? This is the main question answered by this article.
Keywords: analytic hierarchy process; environment, social, and governance; multi-attribute utility theory; multiple criteria decision analysis